Evaluation of Input, Process, and Outputs of Ma’had Ali Program in Islamic Boarding School - Fadil Fadil (Ta'allum: Jurnal Pendidikan Islam, 2020)
Evaluation research aimed at determining the condition of input, process, and output.  evaluation of Input is evaluation of conditions before the Ma'had Ali program was carried out. Process, evaluation of the program management process. Output of the Ma’had Ali Program, at this stage evaluation will be carried out on graduates. Its evaluation model was a countenance stake. The methods were used such as interviews, observation, questionnaires and assessment sheets that are structured for managers, students, lecturers, and alumni. The conclusions of this study were the evaluation of whole input components was in a bad category because the respondents who answered very good and good category were only 50.9% of 100%. Whereas, the evaluation of process components was in a good category because the frequency of very good and good category was 77.17% of 100%, While, the evaluation of the overall output component is in bad category because the frequency of very good and good category was 73.6% of 34 graduates who answered the questionnaire. This shows that the overall output of the Ma’had Ali program has not reached the standard of a successful program.